2020
DOI: 10.1002/mgg3.1140
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Genetic diversity and phylogenetic structure of four Tibeto‐Burman‐speaking populations in Tibetan‐Yi corridor revealed by insertion/deletion polymorphisms

Abstract: Background: Insertion/deletion polymorphisms (InDels), combined with all the desirable features of both short tandem repeat and single nucleotide polymorphism, have been used in archaeological and anthropological research, population genetics and forensic application. Methods: Thirty InDels in 530 individuals residing in the Tibetan-Yi corridor (142 Dujiangyan Tibetans, 164 Muli Tibetans, 187 Xichang Yis, and 37 Yanyuan Mosuos) were genotyped using the Investigator DIPplex. Forensic parameters and allele frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…In our population genetic analyses, compared with other groups, Hainan Han had a closer genetic relationship with Hainan Li, and the genetic relationships among the three populations from the Tibetan-Yi corridor (Dujiangyan Tibetan, Muli Tibetan and Xichang Yi) were closer, which suggested that the genetic relationship is also related to the population geographic origin. These results are similar to the results of population genetic analysis based on other genetic markers, such as SNP [34] and InDel [59]. Similar results were also observed in PCA and MDS analysis.…”
Section: Discussionsupporting
confidence: 88%
“…In our population genetic analyses, compared with other groups, Hainan Han had a closer genetic relationship with Hainan Li, and the genetic relationships among the three populations from the Tibetan-Yi corridor (Dujiangyan Tibetan, Muli Tibetan and Xichang Yi) were closer, which suggested that the genetic relationship is also related to the population geographic origin. These results are similar to the results of population genetic analysis based on other genetic markers, such as SNP [34] and InDel [59]. Similar results were also observed in PCA and MDS analysis.…”
Section: Discussionsupporting
confidence: 88%
“…At present, there are an increasing number of InDel studies based on the CE platform. One of the most researched kits of the Investigator DIPplex kit has been widely used in population studies [4,[39][40][41][42]. In addition, the AGCU InDel 60 kit developed by Liu et al [10] and the 35-plex InDel panel developed by Jin et al [9] were intended for individual identification, and Zhang et al [43] developed a panel including 39 InDels for ancestry inference.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are an increasing number of InDel studies based on the CE platform. One of the most researched kits of the Investigator DIPplex kit has been widely used in population studies [4, 3942]. In addition, the AGCU InDel 60 kit developed by Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…These genetic features are accordance with previous studies using different genetic markers, such as single nucleotide polymorphism, InDel and Microhaplotype. [22][23][24][25] According to the MDS, 10 minorities (Yunnan Miao, Xinjiang Kazakh, 2 Xinjiang Uygurs, Tibet Tibetan, Liangshan Tibetan, Sichuang Tibetan, Hainan Li, Yunnan Dai, Yunnan Zhuang) were isolated on the periphery of the MDS scatter diagrams, and Hui, Manchu and Han populations were gathered in the center. Hui and Manchu populations tend to partially overlap with Han populations, which implying the possible genetic admixture between Han and Hui and Manchu populations.…”
Section: Genetic Similarities and Differencesmentioning
confidence: 99%